Cephalometric Survey on Tengger, Blitar, Kudus and Cililin People - Rio Sofwanhadi; Kunio Abe (Faculty of Dentistry, Universitas Indonesia, 2015)
A cephalometric survey on people of Tengger, Blitar, Kudus and Cililin people has been performed, with the aims to check their hetero/homogeneities, their affinities to mongoloid or austromelanesoid cephalometric characters, their relationship with deutero or protomalayid ancestors and their tendencies toward the presence of cephalometric characteristic polarization. The parameters measured were one stature factor, two neurocranial factors, and ten splancnocranial factors. The survey was cross sectional and on average 50 people of each gender were sampled in all groups. The measurements were done in accordance with Martin Saller method. Age of samples was between 18-25 years. Significant correlation of means of different groups was obtained with 'student t test' with 1% level of confidence. A significant difference was found in the head length and among the cephalic indices between Tengger people and the other groups.The cephalometric characteristics of Tengger people turned out to be closer to protomalayid than to deuteromalayid people, while the cephalometric characteristics of the other groups were closer to mongoloid than to austromelanesoid. They were homogenous without tendency of west-east polarization.